1999
DOI: 10.1152/ajpcell.1999.276.4.c838
|View full text |Cite
|
Sign up to set email alerts
|

Shear-induced tyrosine phosphorylation in endothelial cells requires Rac1-dependent production of ROS

Abstract: The shear-induced intracellular signal transduction pathway in vascular endothelial cells involves tyrosine phosphorylation and activation of mitogen-activated protein (MAP) kinase, which may be responsible for the sustained release of nitric oxide. MAP kinase is known to be activated by reactive oxygen species (ROS), such as H2O2, in several cell types. ROS production in ligand-stimulated nonphagocytic cells appears to require the participation of a Ras-related small GTP-binding protein, Rac1. We hypothesized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
89
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 141 publications
(99 citation statements)
references
References 60 publications
8
89
0
2
Order By: Relevance
“…Rac proteins, in particular rac1, function similarly in nonphagocytic cells, 1,12 and such rac1-regulated ROS have been implicated in a variety of cellular processes including growth, migration, and transformation. 2,8,[12][13][14][15][16][17] We have recently shown that rac1-regulated ROS production also mediates apoptosis in response to I/R. 7 Hepatocyte growth factor (HGF), which was initially isolated as a potent mitogen for hepatocytes, is now known to be a broad-spectrum mitogen for a variety of cell types.…”
Section: Introductionmentioning
confidence: 99%
“…Rac proteins, in particular rac1, function similarly in nonphagocytic cells, 1,12 and such rac1-regulated ROS have been implicated in a variety of cellular processes including growth, migration, and transformation. 2,8,[12][13][14][15][16][17] We have recently shown that rac1-regulated ROS production also mediates apoptosis in response to I/R. 7 Hepatocyte growth factor (HGF), which was initially isolated as a potent mitogen for hepatocytes, is now known to be a broad-spectrum mitogen for a variety of cell types.…”
Section: Introductionmentioning
confidence: 99%
“…However, the experimental setup is not readily applicable to adherent cell types, and the shear forces endemic to the procedure may induce phosphorylation changes that confound the responses to growth factor (10). Here, we present an alternative method for investigating early phosphorylation dynamics in adherent mammary epithelial cells on the timescale of 10 s. Increased temporal resolution, paired with a wide variety of treatment conditions, have provided insight into the mechanisms controlling activation of the EGFR signaling network that are obscured at later time points.…”
mentioning
confidence: 99%
“…All flow studies with cultured ECs, as well as the reoxygenation (RO) phase of hypoxia (H)/RO studies, including work from our group (30,37,48,52,80,81), have been carried out at the atmospheric O 2 concentration (21% O 2 ), which gives rise to a partial pressure of O 2 (PO 2 ) of ϳ160 mmHg, above the levels in arterial blood (75-100 mmHg; 10 -13% O 2 ) and well above the levels in venous blood (35 mmHg; 5% O 2 ) or the levels to which ECs are exposed in tissue capillaries (mean capillary blood PO 2 in the heart is ϳ20 mmHg; 2.6% O 2 ) (72). Since it is known that 1-4% of O 2 reacting with the ETC is incompletely reduced to O 2 ⅐ Ϫ , and the O 2 ⅐ Ϫ formation rate by the ETC complexes III and I increases linearly with O 2 concentration (42,74), we hypothesized that, under flow, the relative "hyperoxic state" of 21% O 2 raises the O 2 concentration in EC mitochondria and enhances the formation of O 2 ⅐ Ϫ , which, via the reaction with shear-induced NO, increases the intramitochondrial ONOO Ϫ levels and potentiates the inhibition of respiration.…”
mentioning
confidence: 99%